IMPLEMENTASI PERDA. NO. 1 TAHUN 2013 TENTANG PEMBAYARAN PAJAK BUMI DAN BANGUNAN PEDESAAN DAN PERKOTAAN DI KECAMATAN PANGEAN KABUPATEN KUANTAN SINGINGI - Atun, Supik; Tua R.F.S, Harapan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Local Government Of Sub-Province Pestle of Singingi have specified Perda. Kab. Pestle of Singingi About PBB-P2. But its fact of execution of payment of land tax and rural building and urban not yet reached goals. This matter is caused by the lack of socialization to masyrakat, lack of coherent sanction of taxpayer tehadap, its minim of data repeat to Iease object and taxpayer. Pursuant to researcher [the] mentioned perform a research about implementation of Perda. No. 1 Year 2013 About payment of land tax and rural building and urban in District Of Pangean Sub-Province Pestle of Singingi. Problem of this research is how implementation of Perda. No. 1 Year 2013 About payment of land tax and rural building and urban in District Of Pangean Sub-Province Pestle of Singingi and factors pursuing implementation of Perda. No. 1 Year 2013 About payment of land tax and rural building and urban in District Of Pangean Sub-Province Pestle of Singingi.Research use theory model Van Meter implementation and Van Horn. Method Research the used is descriptive method qualitative with data collecting technique by interview and observation where party/sides in concerned in policy implementation as informan.Result of analysis that Perda. No.1 Year 2013 About payment of land tax and rural building and urban in District Of Pangean Sub-Province Pestle of Singingi implementation not yet better this matter because of still lack of expense of transportation, data repeat taxpayer which not yet is effective, so also with active addiction pass/through exhortation letter and letter force and also stipulating of goals not yet as according to condition of rill. As for factors able to pursue is awareness of society still less, less impetous government officer do/conduct addiction and socialization.Keyword : Implementation, By Law, Land Tax and Rural Building and Urban.